Sulforaphane: A review of its therapeutic potentials, advances in its nanodelivery, recent patents, and clinical trials. (28th June 2021) - Mangla, Bharti; Javed, Shamama; Sultan, Muhammad Hadi; Kumar, Pankaj; Kohli, Kanchan; Najmi, Asim; Alhazmi, Hassan A.; Al Bratty, Mohammed; Ahsan, Waquar
Abstract : Traditionally, herbal supplements have shown an exceptional potential of desirability for the prevention of diseases and their treatment. Sulforaphane (SFN), an organosulfur compound belongs to the isothiocyanate (ITC) group and is mainly found naturally in cruciferous vegetables. Several studies have now revealed that SFN possesses broad spectrum of activities and has shown extraordinary potential as antioxidant, antitumor, anti‐angiogenic, and anti‐inflammatory agent. In addition, SFN is proven to be less toxic, non‐oxidizable, and its administration to individuals is well tolerated, making it an effective natural dietary supplement for clinical trials. SFN has shown its ability to be a promising future drug molecule for the management of various diseases mainly due to its potent antioxidant properties. In recent times, several newer drug delivery systems were designed and developed for this potential molecule in order to enhance its bioavailability, stability, and to reduce its side effects. This review focuses to cover numerous data supporting the wide range of pharmacological activities of SFN, its drug‐related issues, and approaches to improve its physicochemical and biological properties, including solubility, stability, and bioavailability. Recent patents and the ongoing clinical trials on SFN are also summarized.